Keterampilan Pemecahan Masalah Siswa SMP: Implementasi Model PBL-STEM - Wiwin Rosiningtias; Dadan Rosana; Endang Lutvia Ningseh (Postgraduate, University of Mataram, 2023)
Problem solving skills (PSS) are one of the 21st century skills, but the problems encountered show that students' PSS in science learning are still low, using the PBL model with the STEM approach could be a solution to the students’ problems. So, that the purpose of this study was to determine the effect of applying the PBL model with STEM approach to students' PSS. The method used in this research is quasi experimental method with one group pre-test-post-test design. The research population was students of class VIIA at a SMPN in Jombang. The instrument used was in the form of multiple choice questions with reference to PSS indicators, the data obtained is processed statistically and the results are analysed using n-gain calculations. Based on the results of the analysis, it can be concluded that the application of the PBL model with the STEM approach has an effect on the PSS of students in the moderate n-gain category, when viewed from the PSS indicator, the problem identification indicator gets the highest average of 94% followed by the indicator of setting goals, formulating solutions, and implementing solutions with an average of 72%, and result evaluation indicator with the lowest average of 66%.